2019
DOI: 10.1016/j.mmcr.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous phaeohyphomycosis from Medicopsis romeroi in a diabetic patient

Abstract: Dematiaceous fungi can cause subcutaneous phaeohyphomycosis, an uncommon fungal infection of the dermis and subcutaneous tissues. Medicopsis romeroi is an emerging organism that can infect patients with subcutaneous phaeohyphomycosis, especially immunocompromised patients. The present case involved subcutaneous phaeohyphomycosis caused by Medicopsis romeroi in an 80-year-old Thai male with poorly controlled diabetes, for whom the lesion underwent spontaneous remission after his glycemic control was improved. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…These 52 cases corresponded to 38 cases of PHM, including ours [ 1 , 2 , 3 , 4 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and 14 cases of eumycetoma [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Two cases published as mycetoma by Thiyagarajan et al and Sum et al [ 20 , 21 ] were classified in this review as PHM, regarding the clinical presentation and the lack of grains and bone involvement.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…These 52 cases corresponded to 38 cases of PHM, including ours [ 1 , 2 , 3 , 4 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and 14 cases of eumycetoma [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Two cases published as mycetoma by Thiyagarajan et al and Sum et al [ 20 , 21 ] were classified in this review as PHM, regarding the clinical presentation and the lack of grains and bone involvement.…”
Section: Methodsmentioning
confidence: 88%
“…Subcutaneous PHM is, as shown in our literature review, the most frequently reported clinical presentation (65% of the literature review cases). It is responsible for nodulocystic subcutaneous lesions and abscesses affecting mostly immunocompromised patients with an immunosuppression course ranging from one month to many years [ 1 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 ]. In addition to this typical subcutaneous form of M. romeroi PHM, other presentations were rarely reported, including superficial, disseminated, ocular, and osteoarticular forms.…”
Section: Discussionmentioning
confidence: 99%
“…Phaeohyphomycosis is an uncommon fungal infection occurring more commonly in tropical climates such as India 1 . Most cases have been reported in immunocompromised individuals especially, in diabetics, and in post‐transplant settings 2 . The infection usually results from the traumatic implantation of the causative fungal organism into the subcutaneous tissue and deep dermis.…”
Section: Discussionmentioning
confidence: 99%
“…These differential diagnoses must be ruled out with the growth of dematiaceous moulds on culture and species identification by molecular methods, which is confirmatory. 2,6 The treatment options include surgical excision and oral or systemic antifungal therapy. 3 Adequate control of hyperglycaemia is equally important as seen in the index case.…”
Section: Morphology Quizmentioning
confidence: 99%
See 1 more Smart Citation